The impact of natural and anthropogenic factors on the landforms and landscapes of mountains and their forelands - Prokop, Paweł. Autor; Kijowska-Strugała, Małgorzata. Autor; Wiejaczka, Łukasz. Autor (IGiPZ PAN, 2023)
This paper is an introduction to a collection of nine studies that are intended to fill the gap in the literature associated with landform development and landscape changes related to natural forces and human activities in the Central European Mountains and their close forelands. The papers are grouped into four general categories that describe the influence of climate on glacial landforms and snow avalanches, the evolution of slopes in high mountains, the development of mid-mountain relief, and changes in fluvial systems in mountains and their forelands. This paper summarises the contributions of these studies to this special issue and attempts to outline possible avenues of future research on landforms and landscapes in mountainous areas.
24 cm
Keywords: mountains; geomorphological processes; human impact; landforms; landscapes

Where the Meghalayan meets the Anthropocene: Stratigraphic signals of human-environmental interactions on the periphery of Indian civilisation - Prokop, Paweł. Autor (IGiPZ PAN, 2020)
The aims of this study were to review human-environment interactions during the Meghalayan and to search for the stratigraphic boundary of a new epoch, informally termed the Anthropocene, as well as to determine whether the stratigraphic signals of human activity on the Meghalaya Plateau in Northeast India can be correlated globally. This plateau is the base of the Meghalayan Age that was determined from a speleothem in a cave located on it. Review indicates that study region developed on the periphery of ancient Indian civilisation, with stratigraphic signals of human activity being apparent in only the last few thousand years; that is, substantially later than the neighbouring ancient Indian civilisation. The stratigraphic signals are heterogeneous and diachronous, not only as a result of various human activities, but also in the effect of the diverse sensitivities of the environment to anthropogenic disturbances. A discrete and visible cultural layer that relates to the development of settlements and the production of new materials is still being formed and reworked. The only synchronous stratigraphic signal with a global range seems to be associated with the artificial radionuclide fallout from nuclear weapons testing, which covers a topsoil layer of up to tens of centimetres thick.
24 cm
Keywords: stratigraphy; Holocene; Anthropocene; Meghalaya; human impact

18th-20th century flood-induced changes in the landscapes of the Mała Wisła Valley within the Oświęcimska Basin - Czaja, Stanisław (1949– ) (IGiPZ PAN, 2012)
24 cm
Keywords: floods; changes in landscapes; human impact; Mała Wisła Valley; Poland

Land use changes and their catchment-scale environmenta limpact in the Polish Western Carpathians during transition from centrally planned to free-market economics - Bucała-Hrabia, Anna. Autor (IGiPZ PAN, 2018)
Land use and land cover changes (LULC) and their impact on potential soil erosion, road density as transfer routes of material and water to channels as well as channel level changes were studied in three catchments (~20 km2 each) in the central part of the Polish Western Carpathians in 1975-2015. It was hypothesised that short-term LULC changes during transition from a centrally planned to a free-market economy are sufficient to modify selected elements of the environment and that these changes can be identified in a measurable way. The analysis of aerial photographs and socio-economic data indicates that during the investigated period, the forest area increased by 20-27%, with a continuous decrease of cultivated land by 89-93% in the three catchments. LULC changes were accompanied by continuous population density growth by 29-50% and a decrease of the population dependent only on agriculture to less than 5%. Analyses confirmed the hypothesis that the environment was significantly modified due to the LULC changes. Abandonment of cultivated land, forest succession and a decrease in used road density, have resulted in lower efficiency of slope wash and sediment transport within the 4th-order catchments. This has led to an interruption of aggradation and initiated channel deepening by approximately 1 cm∙year-1 after the introduction of a free-market economy in 1989.
24 cm
Keywords: LULC; human impact; socio-economic transformation; catchment; Carpathians

Spatial diversity of tourist facilities in the Silesian Beskid mountains in Poland - Żemła-Siesicka, Anna. Autor; Andreychouk, Viacheslav. Autor; Myga-Piątek, Urszula. Autor (IGiPZ PAN, 2020)
This article proposes a method of the assessment of distribution of tourist facilities. The main aim of presented study is to assess a spatial density of tourist elements. The evaluation of the distribution of tourist facilities in the landscape allows to indicate overloaded areas. The second purpose is the proposition of an indicator measuring the landscape saturation of tourist facilities, i.e. density index developed by the authors. The index, referred to river basin, is based on the ratio of the area of the tourist facilities to the total area of the unit. For the purposes of calculation, the authors developed a framework for the classification of tourist facilities based on its spatial character. The method was examined in the Silesian Beskid mountain range and can be applied in similar mountain areas.
Keywords: Silesian Beskid; tourist landscape; human impact on landscape; index of tourist facilities density; impact of turist facilities on landscape

Influence of man and climate changes on relief and geological structure transformation in central Poland since the Neolithic - Twardy, Juliusz (1961– ) (IGiPZ PAN, 2011)
187 pp. ; 24 cm
Keywords: human impact; aeolian deposits; slope deposits; fluvial deposits; Neoholocene; Central Poland

Concepts of dynamic equilibrium of interest for river management in the lower Maas catchment - Vandenberghe, Jef; Venhuizen, Gemma; Moor, Jos de (IGiPZ PAN, 2011)
178 pp. ; 24 cm
Keywords: rivers; water management; climate change; human impact; floods; Maas River; Geul River; the Netherlands

Causes and mechanisms of the disappearance of braided channel patterns (the example of the Białka River, Western Carpathians) . - Gorczyca, Elżbieta. Autor; Krzemień, Kazimierz. Autor; Łyp, Michał. Autor; Strużyński, Andrzej. Autor (IGiPZ PAN, 2023)
The channels of multi-threaded (braided) rivers occur commonly in areas that fulfill certain conditions such as substantial influx of bed material and gradients large enough to create significant energy of flowing water. Natural conditions favoring the formation of multithreaded channels are present in the Carpathians in Poland in Podhale – a large basin located in the piedmont area of the high-mountain Tatra massif. The area had experienced glaciation in the Pleistocene. Yet the 20th century – and especially its second half – was a period of rapid and irreversible elimination of braided channels across the region. The Białka is considered to be the last braided river in the Carpathians in Poland. Many parameters like: structure (morphologic reach sequence), degree of braiding (BI index, W/D) and also a number of hydrodynamic ones (unit stream power, critical stress, shear stress, others) were investigated in order to assess a current stage of development of the Białka river channel. The Białka river channel appears to be a complex system with a differentiated structure. Its channel system is a mosaic of different types described by the following sequence: straight-sinuous-braided. It represents an intermediate type that is somewhere between a single- and a multi-threaded channel. Future evolution of the Białka river channel appears to include further degradation and transformation into a poorer channel ecosystem.
24 cm
Keywords: multi-threaded river channel; wandering channel; hydromorphologic analysis; human impact; Białka River; Polish Carpathians

Prawidłowości obiegu wody na obszarze beskidzko-pogórskim Karpat Zachodnich na przykładzie zlewni Bystrzanki w świetle zmian klimatu i działalności człowieka = Regularities of the water cycle in the Western Carpathians Beskids-foothills area based on th - Bochenek, Witold. Autor (Instytut Geografii i Przestrzennego Zgospodarowania im. Stanisława Leszczyckiego, Polska Akademia Nauk, 2020)
182 pages : color illustrations ; 24 cm
Bibliography on pages 163-177
English summary
Keywords: hydrology; climate change; human impact; Bystrzanka catchment

Recent advances on geomorphology of the Gorce Mountains, the Outer Western Carpathians – state-of-the-art and future perspectives - Kroh, Paweł. Autor; Pawlik, Łukasz. Autor (IGiPZ PAN, 2021)
The increase of geomorphological research during the last decades in the Gorce Mts. caused the need for state-of-art review papers. The Gorce Mountains were formed as an isolated massif with Mt Turbacz (1310 m a.s.l.) as the highest summit. River channels are remodeled by sudden and high-level floods with the critical impact of log jams. The main processes influencing hillslope relief were landsliding, run-off, and tree uprooting. The review suggests the following issues await for studies: a long-term landscape evolution, monitoring of morphogenetic processes, and origin of landslides with their contribution to denudation rates. Also, current biomorphodynamics (uprooting process) has not been sufficiently studied.
24 cm
Keywords: geomorphology; relief; landslides; hillslope processes; fluvial processes; human impact; biomorphodynamics

Następstwa zaniku antropopresji na obszarach górskich – dyskusja zależności „proces a region” w ujęciu różnoskalowym = Consequences of the disappearance of human impact from mountainous areas – a discussion of “process vs. region” relationships as conceptualized on various scales - Wolski, Jacek (IGiPZ PAN, 2009)
24 cm
Keywords: dissapearance of human impact; depopulated areas; multiscale analysis; mountain regions of Poland and Europe

Zapis zmian klimatu oraz działalności człowieka i ich rola w holoceńskiej ewolucji dolin środkowoeuropejskich = Reflection of climatic changes and human activity and their role in the Holocene evolution of Central European valleys - Kalicki, Tomasz (1958– ) (IGiPZ PAN, 2006)
348 pp., [8] l. pl., [2] l. pl. col. : ill. ; 24 cm
Bibliogr. p. 303-346
Summ. eng.
Keywords: river valleys; river valleys evolution; dating of sediments; alluvia; records of human impact in valleys; records of climate change in valleys; palaeoclimate; Holocene; Central Europe

Przegląd Geograficzny T. 67 z. 3-4 (1995) (IGiPZ PAN, 1995)
24 cm
Keywords: Institute of Geography and Spatial Organization Polish Academy of Sciences; big cities; urbanization; palaeogeography; loess areas; accumulation of loess; agriculture; geopolitics; trade; services; border aeas; rivers; discharges; tills; physico-geographical regionalization; natural radioactivity; small water objects; ice-morainic ramparts; Poland; Europe; Finland; Kaliningrad District; Eastern Poland; Mongolia; Wielkopolska Region; Eastern Europe; Sudety Mountains; France; Spitsbergen